Pengembangan Aplikasi Administrasi Kependudukan Berbasis Web di Kantor Pemerintahan Desa Gorowong menggunakan Metode SDLC dengan Model Waterfall - Indika Hanjalah; Arif Rahman; Mohamad Sopiyan; Opa Fauzi; Yulianti Yulianti; Aries Saifudin; Niki Ratama (Teknik Informatika Universitas Pamulang, 2022)
There is no doubt that the progress of data innovation is growing rapidly which facilitates human work, one of which is in the field of population organization. Gorowong village is one of the villages in the city of Bogor. This research is motivated by the problems that exist in the village of Gorowong, where in carrying out services and data collection the population still uses conventional methods, using Microsoft Excel which must be inputted one by one, and if the file is deleted it can cause data loss. The community must handle the required documents at government agencies by following existing procedures, so if the community has a need related to letters or anything, the community must come directly to the gorowong village government office. This population administration application planning uses the SDLC (System Development Life Cycle) research technique with the Waterfall model, which in this method describes the technique of drawing direct and sequential programming development techniques (waterfall). The information collection strategy used includes 3 techniques, particularly observation, interview, and literature studies. This research produces several application designs including use case diagrams, database relations, ERD, and architectural design. This application has been completed according to the client's wishes and will continue to be monitored and updated. Aims to facilitate all population administration processes in Gorowong village, and there is no need to use conventional methods anymore.